Over the limit? Testing non‐linear associations between alcohol outlets and young adults' alcohol consumption. (22nd June 2020) - Foster, Sarah; Hooper, Paula; Divitini, Mark; Knuiman, Matthew; Trapp, Georgina
Abstract: Introduction and Aims: By specifying a threshold at which the number of liquor licences has the most impact on local populations, authorities can work to restrict licence approvals and help prevent alcohol‐related harm. Design and Methods: Raine Study Generation 2 participants reported their alcohol intake at 22 years ( n = 843) and liquor licences within 1600 m of participants' homes were mapped. Analyses examined associations between licences (all licences, on‐premise licences, liquor stores) and alcohol intake (g ethanol per day). Two models were fitted: (i) forced a straight‐line relationship; and (ii) allowed a curved relationship via restricted cubic splines. Results: The straight‐line and curved models showed significant relationships with all licences ( P = 0.002 and P = 0.002 respectively) and on‐premise licences ( P = 0.006 and P = 0.01 respectively), but not liquor stores ( P = 0.065 and P = 0.13 respectively). The straight‐line model indicated that alcohol consumption increased, on average, by 0.15 g per day for each additional licence and 0.17 g per day for each additional on‐premise licence. The curved model indicated that consumption increased by around 0.4 g per day for each additional licence from 0 to 10, but increases were negligible for additional licences beyond 10. The curved model provided a better overall fit to the data than the straight‐line model ( R 2 9.52% vs. 9.18%), but the improvement in fit did not quite reach statistical significance ( P = 0.08). The curvature was similar, but less pronounced for on‐premise licences ( R 2 9.11% vs. 8.95%; P = 0.23). Discussion and Conclusions: Results suggest a possible saturation point at which additional licences have a smaller effect on the alcohol intake of 22‐year‐olds living in metropolitan Perth.